Thismia pseudomelanomitra (Thismiaceae), a new mycoheterotrophic species from Brazilian Amazon Forest - Ferreira Da Silva, Diego; Da Silva Ribeiro, Ricardo; Marcelo Alvarenga Braga, João (Phytotaxa, 2023)
A new species of Thismia is described and illustrated for the Brazilian Amazon Forest. Thismia pseudomelanomitra belongs to Thismia subg. Ophiomeris sect. Pyramidalis and is morphologically similar to T. melanomitra. However, it can be recognized by its orbicular outer tepals with revolute margins, inner tepals connate over the tube opening forming a subglobose mitre, outer surface bearing prominent irregularly dentate ribs and irregularly foveae on top. The new species is known from a single locality, collected at São Nicolau Farm, in the northwest of Mato Grosso State. Herein, we provide a detailed description with illustrations, photographic plates, distribution maps, and preliminary conservation status.